Is there asymmetry in forward exchange rate bias? Multi-country evidence - Su Zhou; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This study illustrates that the empirical rejection of the forward rate unbiasedness hypothesis is not sensitive to whether the forward U.S. dollar is quoted at a premium or a discount. It is argued that the reported finding of so-called asymmetry in forward exchange rate bias in earlier work is simply due to the inclusion of a sample period during which a forward rate anomaly exists.
Keywords: F31; G15; 330; Asymmetry in forward exchange rate bias; Forward rate anomaly; Devisentermingeschäft; Wechselkurs; Schätzung; US-Dollar; Welt